Psychology in action - Huffman, Karen (Hoboken, NJ John Wiley & Sons, Inc., 2007)
Covering the various major concepts and theories, this work presents the practical applications of psychology.
Includes bibliographical references (pages R1-R52) and indexes.
Keywords: Psychology -- Textbooks